Effects of B and P Doping on Electronic Structure and Lithium Diffusion Properties of Si(100) Surface. Issue 3 (25th December 2022) - Yan, Gongqin; Xu, Tianqi; Hu, Miao; Xi, Yidong; Lan, Chunbo
Abstract: Surface and lithium diffusion properties of Si(100) doped with B and P are studied using first‐principles plane wave pseudopotential method. The calculated results show that B‐doping has a greater effect on Si(100)‐7 than P‐doping. For 0.5 mol% P‐doping, the population difference between Si5─P bonds and Si5─Si3 bonds is 0.02. For 0.5 mol% B doping, the bond population of Si5─B is 1.8 times that of Si5─Si3 and the structure fluctuates greatly. The migration of a single Li atom from V and B sites on the structure's surface to an orthotetrahedral site inside the structure is simulated. Simulation results show that with the increase of P doping concentration from 0 to 1.0 mol%, the Li diffusion rate is ordered as 0.5 mol% < 0 mol% < 1.0 mol%. Furthermore, the ab initio molecular dynamics method is used to simulate the diffusion of multiple Li atoms in P‐doped Si(100)‐7. When the simulation time is longer than 0.09 ps, the Li diffusion rate is ordered as 0.5 mol% < 0 mol% < 1.0 mol%. Doping Si(100) surface with P could effectively reduce the diffusion barrier for Li atoms in it. Abstract : The diffusion of a single and multiple Li atoms are calculated. For doping with P, the Li diffusion rate is 0.5 mol% < 0 mol%<1.0 mol%. When the simulation time is greater than 0.09 ps, the diffusion rate of Li is 0.5 mol% < 0 mol%< 1.0 mol% as well.